Arable lands degradation in the northern steppe zone of Ukraine - Kharytonov, Mykola; Харитонов, Микола Миколайович; Pashova, Valentina; Пашова, Валентина Трифонівна; Bagorka, Maria; Багорка, Марія Олександрівна; Kozechko, Vladimir; Козечко, Володимир Іванович; Dudar, Tamara; Дудар, Тамара Олександрівна (Biotechnical Faculty of the University of Montenegro, 2016)
The case study is devoted to the agroecological peculiarities of the eroded soils fertility taking into account their genesis and morphology. The researched soils are located on the slopes of different exposure in the subzone of ordinary black mollisols. The laboratory and field observation of the eroded soils was carried out on the base of training farm ”Samarsky”. The research of quantitative and qualitative composition of physical and chemical qualities in arable soils on the slopes and watersheds was performed. On the basis of it the dependence between the eroded soils fertility and environmental conditions was established. On their genesis, the slope soils are represented by the variety of watershed types of black mollisols. These soils are considered as special more arid soils additionally superimposed with erosion process. They represent genetic forms of intrazonal and zonal types. The humus content in the 0-30 cm layer in the plain amounted to 4.1 %, while decreasing on the northern exposure slope by one third, and on the southern exposure slope – twice. The qualitative humus change was observed: the humic acid content decrease when insignificant change of fulvic acids. Тематичний аналіз присвячений агроекологічним особливостям родючості еродованих ґрунтів з урахуванням їх генезису та морфології. Досліджувані ґрунти розташовані на схилах різної експозиції в підзоні чорних молізолів звичайних. Лабораторне та польове обстеження еродованих ґрунтів проводилось на базі навчального господарства «Самарський». Проведено дослідження кількісного та якісного складу фізико-хімічних властивостей орних ґрунтів на схилах та вододілах. На його основі встановлено залежність між родючістю еродованих ґрунтів та екологічними умовами. За генезисом схилові ґрунти представлені різноманіттям вододільних типів чорних молізолів. Ці ґрунти розглядаються як особливі більш посушливі ґрунти, на які додатково накладається процес ерозії. Вони представляють генетичні форми інтразонального та зонального типів. Вміст гумусу в шарі 0-30 см на рівнині становив 4,1 %, при цьому на схилі північної експозиції він зменшився на третину, а на схилі південної експозиції – вдвічі. Спостерігається якісна зміна гумусу: при незначній зміні фульвокислот знижується вміст гумінових кислот.
Деградація орні земель Північного степу України
Keywords: degradation; деградація; soil; ґрунт; slope; ухил; genesis; genesis; fertility; родючість; humus; гумус